Analisis Intellectual Capital Terhadap Net Profit Margin pada Perusahaan Asuransi - Hermaya Ompusunggu; Dian Efriyenti; Aura Adenilla (Prosiding, 2020)
This study aims to analyze intellectual capital on net profit margin. The sample collection technique used is purposive sampling, from 14 insurance companies listed on the Indonesia Stock Exchange, which meet the sample criteria of 11 companies. The data analysis method used in this research is by using SPSS software. From the data analysis, the results show that partially, human capital has a significant effect on net profit margin where human capital has a tcount of 7.687 with a significance of 0.000 smaller with a significance level of 0.05, so Ho1 is rejected and Ha1 is accepted. Structural capital has a significant effect on net profit margin. where structural capital has a tcount of 5,500 with a significance of 0,000, smaller with a significance level of 0.05, so Ho2 is rejected and Ha2 is accepted. Relational capital has an effect on but not significant to net profit margin where relational capital has a tcount of 1.214 with a significance of 0.230, which is greater with a significance level of 0.05, so Ho3 is accepted and Ha3 is rejected, and simultaneously, human capital, structural capital and relational capital have a significant effect on net profit margin where the regression value has a significance of 0.000, a value less than 0.05 or a significant value <α so that Ho4 is rejected and Ha4 is accepted.